Pengelolaan Zakat di Indonesia - Ahdiyat Agus Susila (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2018)
Zakat is one of worship in Islam with personal, social and economic dimension. In an economic review, zakat is the main instrument of the state's fiscal policy to distribute equitable wealth and prosperity. Therefore, management management mechanisms should receive serious attention. Zakat managers must be able to carry out the mandate of realizing the potential of extraordinary zakat, especially in Indonesia. Based on a study conducted Baznaz in collaboration with IPB and Islamic Development Bank in 2011, the potential of zakat acceptance of all Muslims in Indonesia for Rp. 217 trillion rupiah.